Sport Facilities Planning, Design, Operation, and Management Trends: An Introduction to the Special Issue - Jeffrey Petersen; Lawrence W Judge (Journal of Applied Sports Management, 2023)
The focus of this special issue is to grow the existing academic literature on sport facilities. This is done by presenting a variety of perspectives from established and emerging scholars in the field. The aim of this special issues aligns with the mission of the Journal of Applied Sport Management, which is to publish research and conceptual contributions that bridge the gap between scholarly work and professional practice in sport business. In all, the special issue includes five thought-provoking pieces contributed by 12 authors as well as a practitioner interview with Earl Santee, one of the most acclaimed sport designers in the world.
Keywords: Facility Design; Operation Management; Sport Facilities; Training